2019
DOI: 10.1002/bdr2.1630
|View full text |Cite
|
Sign up to set email alerts
|

PBX‐WNT‐P63‐IRF6pathway in nonsyndromic cleft lip and palate

Abstract: Nonsyndromic cleft lip and palate (NSCLP) is one of the most common craniofacial anomalies in humans, affecting more than 135,000 newborns worldwide. NSCLP has a multifactorial etiology with more than 50 genes postulated to play an etiologic role. The genetic pathway comprised of Pbx-Wnt-p63-Irf6 genes was shown to control facial morphogenesis in mice and proposed as a regulatory pathway for NSCLP. Based on these findings, we investigated whether variation in PBX1, PBX2, and TP63, and their proposed interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 75 publications
0
19
1
1
Order By: Relevance
“…TP63 is a canonical WNT signaling target, and has been recently implicated in NSCL/P in both a GWA meta‐analysis and exome‐sequencing study (Basha et al, 2018; E. J. Leslie et al, 2017). A recent study that identified the first OFC association with Pre‐B cell leukemia homeobox 1 ( PBX1 ) and PBX2 mutations also identified gene‐gene interactions between SNPs in PBX1 and WNT9B , and between IRF6 and each of PBX1 , PBX2 , and TP63 in the etiology of NSCL/P (Maili et al, 2019). These findings are consistent with a prior study that linked Pbx, p63, and Irf6 with Wnt signaling in midfacial development in animal models (Ferretti et al, 2011).…”
Section: Genetics Of Human Ofcsmentioning
confidence: 99%
See 1 more Smart Citation
“…TP63 is a canonical WNT signaling target, and has been recently implicated in NSCL/P in both a GWA meta‐analysis and exome‐sequencing study (Basha et al, 2018; E. J. Leslie et al, 2017). A recent study that identified the first OFC association with Pre‐B cell leukemia homeobox 1 ( PBX1 ) and PBX2 mutations also identified gene‐gene interactions between SNPs in PBX1 and WNT9B , and between IRF6 and each of PBX1 , PBX2 , and TP63 in the etiology of NSCL/P (Maili et al, 2019). These findings are consistent with a prior study that linked Pbx, p63, and Irf6 with Wnt signaling in midfacial development in animal models (Ferretti et al, 2011).…”
Section: Genetics Of Human Ofcsmentioning
confidence: 99%
“…Pbx ‐induced Wnt signaling activates Tp63 , which in turn activates Irf6 to promote epithelial apoptosis, and disrupting these interactions results in CL/P (Ferretti et al, 2011). While this sequence was initially identified in mice, a recent study reported gene‐gene interactions between several of these factors in association with NSCL/P in human patients, likely demonstrating a conserved mechanism of regulating lip fusion (Maili et al, 2019). Tp63 also represses Bmp and promotes Shh and Fgf signaling, and Tp63 ‐null mouse embryos have bilateral CPO (Thomason et al, 2008).…”
Section: Wnt Signaling In Ofcsmentioning
confidence: 99%
“…The genetic basis of nsCL/P is complex, and until now, not well understood [ 47 ]. So far, more than 50 genes have been identified for the pathogenesis of nsCL/P [ 48 ] and more than 260 for the syndromic phenotypes [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of genes are involved in nonsyndromic forms of orofacial clefts, including above all growth factors ( CLPTM1 , FGFR1, TGFA, TGFB3 ), genes related to nutritional metabolism ( GAD1 , LRP6, MTHFR ) and transcription factors ( GRHL3, IRF6, MSX1, TBX1, TBX22, TP63 ) [ 10 , 14 , 15 ]. Unfortunately, we could not further investigate these genes because the parents refused any further genetic examination.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced maternal age, some maternal medications, cigarette smoking and folate deficiency have been associated with the risk of isolated orofacial clefts in offsprings [ 9 ]. Although of complex heterogenetic origin, syndromic cleft palate might be associated with variants in a single gene or in a cluster of contiguous genes (copy number variants), such as van der Woude syndrome, 22q11-deletions syndrome, or chromosomopathies [ 9 , 10 ]. Furthermore, in non-syndromic orofacial clefts more than 50 genes as well as additive gene-gene and gene-environment interactions, with modifier phenotypic effects, are postulated to play an etiologic role.…”
Section: Introductionmentioning
confidence: 99%